1997
DOI: 10.1046/j.1365-2494.1997.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of diploid and tetraploid perennial ryegrass and tetraploid ryegrass/white clover swards under continuous sheep stocking at controlled sward heights. 3. Sward characteristics and animal output, years 4–8

Abstract: Results for years 4–8 of a long‐term grazing experiment on swards of a diploid perennial ryegrass (Lolium perenne), var. Contender (D swards), a tetraploid ryegrass, var. Condesa (T swards) and Condesa with S184 white clover (Trifolium repens) (TC swards), direct sown in May 1987, are presented. The swards were continuously stocked with sheep from 1988 to 1990, as previously reported, and for a further 5 years, 1991–95, at a target sward surface height (SSH) of 4–6 cm. Control of sward height was successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
2
10
2
1
Order By: Relevance
“…Contrary to our study, in several comparative grazing studies, production gain ha −1 for sheep was greater for tetraploid perennial ryegrass than their diploid counterparts (Davies, Fothergill, & Jones, ; Davies, Fothergill, & Morgan, ; Evans et al., ; Vipond, Swift, Cleland, Fitzsimons, & Hunter, ; Vipond et al., ). The greater liveweight gain ha −1 (6% – 16%) for tetraploid compared to diploid ryegrass swards was attributed to the 10% greater SR for the tetraploid sward because of the generally greater herbage mass (Vipond et al., , ). The linear decrease in ADG with increasing SR observed in this study is a common response that has been reported in numerous other studies (e.g., Derner, Hart, Smith, & Waggoner, ; Gunter, Beck, Hutchison, & Phillips, ; Inyang et al., ; Morgan et al., ; Phillips, Hart, Glimp, & Vontungeln, ; Sharrow et al., ; Stewart et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our study, in several comparative grazing studies, production gain ha −1 for sheep was greater for tetraploid perennial ryegrass than their diploid counterparts (Davies, Fothergill, & Jones, ; Davies, Fothergill, & Morgan, ; Evans et al., ; Vipond, Swift, Cleland, Fitzsimons, & Hunter, ; Vipond et al., ). The greater liveweight gain ha −1 (6% – 16%) for tetraploid compared to diploid ryegrass swards was attributed to the 10% greater SR for the tetraploid sward because of the generally greater herbage mass (Vipond et al., , ). The linear decrease in ADG with increasing SR observed in this study is a common response that has been reported in numerous other studies (e.g., Derner, Hart, Smith, & Waggoner, ; Gunter, Beck, Hutchison, & Phillips, ; Inyang et al., ; Morgan et al., ; Phillips, Hart, Glimp, & Vontungeln, ; Sharrow et al., ; Stewart et al., ).…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the results of other studies. Orr et al (2005) reported that diploid cultivars had greater tiller density than tetraploid cultivars in pastures grazed by beef heifers (up to 11,000 vs. 8360 tillers m −2 , respectively) and Vipond et al (1997) found similar results in pastures grazed by sheep (3-year mean 16,000 and 13,700 tillers m −2 , respectively).…”
Section: Effects Of Ryegrass Typementioning
confidence: 80%
“…These increases in forage quality have led to increases in milk (Castle and Watson 1971) and meat production (Vipond et al 1993(Vipond et al , 1997 when combined with appropriate grazing management.…”
Section: Introductionmentioning
confidence: 99%